Penegakan Hukum Ketenagakerjaan terhadap Eksploitasi Generasi Z dalam Kontrak Kerja Jangka Pendek (PKWT): Perspektif Keadilan Sosial - Mahesa, Nehanis; Amelia, Regita Nur; Putri, Tania Syah (Journal of Information Systems and Management (JISMA), 2025)
This study analyzes the phenomenon of exploitation of Generation Z workers through the Fixed-Term Employment Agreement (PKWT) scheme and the effectiveness of labor law enforcement from a social justice perspective. Generation Z (born 1997-2012) entering the labor market face repeated PKWT practices that violate the Manpower Law. The research method uses a normative juridical approach with a qualitative descriptive analysis of labor regulations and case studies of law enforcement. The results show that the use of PKWT against Generation Z often deviates from the provisions of Article 59 of Law No. 13 of 2003 in conjunction with the Job Creation Law, with contract extension patterns inconsistent with the substance of permanent employment. Law enforcement by the Labor Inspectorate remains weak due to limited resources and administrative sanctions that do not provide a deterrent effect. From a Pancasila social justice perspective, this practice contradicts the fifth principle, which guarantees workers' welfare. The study recommends strengthening labor supervision, increasing sanctions for violators, and educating Generation Z about workers' rights to achieve social justice in industrial relations.